LIFELONG LEARNING FOR TALENT MANAGEMENT AND PROFESSIONAL DEVELOPMENT OF EMPLOYEES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2023)
The new challenges in almost all organisations are based on people. It is their competences, knowledge and skills that enable any organisation to grow. Personnel are a resource that must be properly taken care of. Effective talent management is mainly based on planning and building career paths. Talent management is one of the most important business priorities for organisations that care about achieving business goals, knowledge management and managing staff potential. Research shows that entities that identify and manage talent produce 15 per cent higher results for their stakeholders compared to pillars that do not run such programmes.The aim of this article is to present the activities carried out within the framework of TALENT MANAGEMENT ERASMUS+ project nr 2021-2-ES01-KA210-ADU-000048687, which is dedicated to economically active employees over 45 years of age and promotes integration in the labour market.